IMPROVING THE EFFECTIVENESS OF EVAPORATION IN SOLAR DISTILLATION UNITS THROUGH AIR FEEDING IN THE EVAPORATION CABIN - Irwansyah; Zulfikar; Asnawi (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2019)
Solar distillation has been used to distill seawater into clean water. The distillation process is largely determined by the effectiveness of the evaporation and condensation processes. This study aimed to investigate the method of condensing air into the water and evaporator space on the effectiveness of the evaporation process. The solar distillation is designed as two units with a single basin type. Type-I solar distillation is designed with the evaporator and condenser chambers in one room. The solar distillation type-II is designed with a modified evaporator chamber so that water vapor can be circulated out and without a condenser room. The solar distillation length and width are 600 mm and 400 mm, respectively, which are made of a 0.6 mm thickness stainless steel plate. At the top, it is covered by a 5 mm thickness glass with a slope of 10°. The test was carried out for 7 days together between the type-I solar distillation and the type-II solar distillation. Data on raw water temperature, room temperature, glass surface temperature, ambient temperature, and solar intensity were recorded during the test. The data is recorded every 30 minutes starting at 08.00 GMT+7 until 17.30 GMT+7. The test results show that the solar distillation performance is influenced by the high and low solar intensity. The volume production of water vapor in the type-II solar distillation is greater than that of the type-I solar distillation. This shows that condensing air into the water and evaporator space can increase the evaporation process's effectiveness on the solar distillation.